Use of Adjunctive Therapy in Acute Kawasaki Disease in Latin America - Fortuna-Reyna, Brenda; Bainto, Emelia V.; Ulloa-Gutierrez, Rolando; Garrido-García, Luis M.; Estripeaut, Dora; del Águila, Olguita; Gómez, Virgen; Faugier-Fuentes, Enrique; Miño-León, Greta; Beltrán, Sandra; Cofré, Fernanda; Chacón-Cruz, Enrique; et al. (Frontiers in Pediatrics, 2020)
Objective: To characterize the use of adjunctive therapy in Kawasaki disease (KD) in Latin America. Methods: The study included 1,418 patients from the Latin American KD Network (REKAMLATINA) treated for KD between January 1, 2009, and May 31, 2017. Results: Of these patients, 1,152 received only a single dose of IVIG, and 266 received additional treatment. Age at onset was similar in both groups (median 2 vs. 2.2 years, respectively). The majority of patients were male (58 vs. 63.9%) and were hospitalized with the first 10 days of fever (85.1 vs. 84.2%). The most common adjunctive therapy administered was steroids for IVIG-resistance, followed by additional doses of IVIG. The use of biologics such as infliximab was limited. KD patients who received adjunctive therapy were more likely to have a lower platelet count and albumin level as well as a higher Z score of the coronary arteries. Conclusion: This is the first report of adjunctive therapies for KD across Latin America. IVIG continues to be the initial and resistance treatment, however, steroids are also used and to a lesser extent, biological therapy such as infliximab. Future studies should address the barriers to therapy in children with acute KD throughout Latin America.